Challenges of Dermanyssus gallinae in Poultry: Biological Insights, Economic Impact and Management Strategies - Péter Sárkány; Zoltán Bagi; Ágnes Süli; Szilvia Kusza (Insects)
Bird mites are parasites that feed on both wild and domesticated bird species, causing severe degradation in avian welfare. The chicken mite, Dermanyssus gallinae in particular, is a widespread ectoparasite in poultry, responsible for several challenges faced by the poultry industry, including poor animal health, which causes significant economic losses. This review, based on our current knowledge, aims to provide a comprehensive insight into the biology and distribution of these mites, as well as their impact on poultry health and production. It explores the most prevalent mites in avian species, with a focus on D. gallinae, and examines the different psychological and physiological alterations observed in infected stocks, such as decreased egg production, weight loss, and an increased susceptibility to diseases. This review will also cover existing control strategies, including chemical, biological, and environmental approaches, with attention to the growing concern around pesticide resistance. Additionally, it delves into genetic research conducted on these mites, primarily focusing on phylogenetic studies, which have provided insights into their evolutionary relationships and potential vulnerabilities. By compiling existing studies, this article underscores the urgent need for effective and sustainable countermeasures, as well as further genetic research to mitigate the substantial impact of D. gallinae on the poultry sector.